Process optimization and flavor composition analysis of tea-flavor distilled liquor - WANG Jiangbo, XIA Xiao, MAO Chunkui, CHEN Jiahao, HE Chao, CAI Fengjiao, ZHANG Ruijing, XU Jian (Zhongguo niangzao, 2025)
To improve the utilization rate of tea by-products, tea-flavor distilled liquor was prepared by traditional solid-state fermentation using fresh malt and green tea stems as mixed fermentation raw materials. Using sensory score and ethyl acetate content as evaluation indices, the fermentation process was optimized based on single factor tests and central combination design (CCD) tests as well as artificial neural network (ANN) analysis combined with genetic algorithm, and the volatile aroma components of the liquor samples were determined by gas chromatography-mass spectrometry (GC-MS). The results showed that the optimal fermentation conditions were green tea stems addition 7%, cooked grain moisture 52%, Jiuqu addition 0.7%, fermentation time 7 d, and temperature 25 ℃. Under the optimized conditions, the ethyl acetate content of the tea-flavor distilled liquor was 0.46 g/L, the sensory score was 86.67 points, and the alcohol content was 55%vol. A total of 31 volatile flavor compounds were detected based on GC-MS, including 5 alcohols, 16 esters, 5 aldehydes and 5 others. Esters had the highest content, accounting for 52% of all flavor compounds. Tea-flavor distilled liquor possessed robust tea aroma, agreeable mellow taste and distinctive flavor, which served to enhance the character of the tea liquors to a notable degree.